The Edward R. Murrow collection [videorecording (DVD)] : The best of See It Now - Murrow, Edward R.; Wallace, Mike, 1918-2012 (Docurama ; Distributed by New Video, 2005)
Hosted by Mike Wallace, Walter Cronkite, and Dan Rather, this set explores the life and groundbreaking work of Edward R. Murrow, America's most esteemed broadcast journalist.